The Use Of Mother Tongue In English Classrooms - Анорбоева, Диёра (Журнал иностранных языков и лингвистики, 2023)
The use of mother tongue in teaching a foreign language is a controversial topic. While some researchers claim that the mother tongue should not be used in foreign language classrooms, others think that it makes a valuable contribution to the learning process. In different methods and approaches, the role of mother tongue is different. This article is aimed at promoting and enhancing the use of English language in EFL classes and at the same time allowing the mother tongue to be used in particular situations.